2004
DOI: 10.1093/ajcn/80.2.410
|View full text |Cite
|
Sign up to set email alerts
|

Copper, selenium, zinc, and thiamine balances during continuous venovenous hemodiafiltration in critically ill patients

Abstract: CRRT results in significant losses and negative balances of selenium, copper, and thiamine, which contribute to low plasma concentrations. Prolonged CRRT is likely to result in selenium and thiamine depletion despite supplementation at recommended amounts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
156
2
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(172 citation statements)
references
References 22 publications
6
156
2
8
Order By: Relevance
“…First, high-intensity CRRT removes more beneficial substances, counteracting the beneficial removal of harmful compounds. Beneficial substances include micronutrients such as water-soluble vitamins, trace elements, amino acids and circulating beneficial mediators of whatever kind [23,24]. In particular, hypophosphatemia may play a role as its incidence was increased by highintensity CRRT in the original trial from which the current nested cohort was taken [7].…”
Section: Survivalmentioning
confidence: 99%
“…First, high-intensity CRRT removes more beneficial substances, counteracting the beneficial removal of harmful compounds. Beneficial substances include micronutrients such as water-soluble vitamins, trace elements, amino acids and circulating beneficial mediators of whatever kind [23,24]. In particular, hypophosphatemia may play a role as its incidence was increased by highintensity CRRT in the original trial from which the current nested cohort was taken [7].…”
Section: Survivalmentioning
confidence: 99%
“…Effluent losses of copper during CRRT are about 400 µg/d [39,40]. This is nearly 50% of the DRI and falls well within the recommended parenteral intake range of 300 to 500 µg/d [41].…”
mentioning
confidence: 53%
“…Selenium in CRRT fluids is negligible but losses in CRRT effluent have been observed in the range of 35 to 91 µg/d [39,40]. This amount is at or exceeds the DRI as well as the recommended parenteral intake of selenium [41].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have found thiamine deficiency to be prevalent in different critically ill conditions, such as prolonged parenteral nutrition, dialysis, post bariatric surgery, and burns. Importantly, thiamine deficiency is also prevalent in patients with septic shock, with rates ranging from 20% to 70%, depending on study design (7)(8)(9)(10). In addition, elevated concentrations of serum lactate, metabolic acidosis, and hypotension occur in both thiamine deficiency and septic shock.…”
mentioning
confidence: 99%